Multi-mode adaptive control strategy for a lower limb rehabilitation robot - Liang, Xu; Yan, Yuchen; Dai, Shenghua; Guo, Zhao; Li, Zheng; Liu, Shengda; Su, Tingting (Frontiers in Bioengineering and Biotechnology, 2024)
Different patients have different rehabilitation requirements. It is essential to ensure the safety and comfort of patients at different recovery stages during rehabilitation training. In this paper, a multi-mode adaptive control method is proposed to achieve a safe and compliant rehabilitation training strategy. First, patients' motion intention and motor ability are evaluated based on the average human-robot interaction force per task cycle. Second, three kinds of rehabilitation training modes, namely, robot-dominant mode, patient-dominant mode and safety-stop mode, are established, and the adaptive controller can dexterously switch between the three training modes.In the robot-dominant mode, based on the motion errors, the patient's motor ability and motion intention, the controller can adaptively adjust its assistance level and impedance parameters to help patient complete rehabilitation task and encourage the patient to participate actively. In the patient-dominant mode, the controller only adjusts the training speed. When the trajectory error is too large, the controller switches to the safety-stop mode to ensure patient safety. Then, the stabilities of the adaptive controller under three training modes are proved by using Lyapunov theory. Finally, the effectiveness of the multi-mode adaptive controller is verified by simulation results.